Significance of Interleukin-33 and Its Related Cytokines in Patients with Breast Cancers - Liu, Jing; Shen, Jia-Xin; Hu, Jia-Lin; Huang, Wen-He; Zhang, Guo-Jun (Frontiers in Immunology, 2014)
Interleukin-33 (IL-33) is a recently identified cytokine, an important member of the IL-1 family. IL-33 binds to its receptor ST2 to induce type 2 cytokines and exert both pro-inflammatory and protective functions in host defense and disease. Murine breast carcinoma models suggest disruption of ST2 signaling may enhance the anti-tumor immune response, suggesting IL-33 impedes anti-tumor immunity. However, the role of IL-33 in patients with breast cancers is not elucidated. We detected the expression of IL-33 in tumor tissue, and IL-33 and its related cytokines in serum from breast cancer patients. Using Luminex and immunohistochemistry methods, we found that serum levels of IL-33 were nearly 2-fold higher in patients with breast cancers, compared to patients with benign breast diseases. In cancer tissues, expression of IL-33 was higher than matched normal breast tissues from the same patients, and was also associated with a well-differentiated phenotype, HER2 overexpression, more lymph nodes involvement, and a family history of malignant carcinoma. These results suggest that IL-33 may play an important role in the progress of breast cancers and may be a useful biomarker for predicting the progress and metastasis of breast cancers.